INTRAUTERINE GROWTH IN SELECTED NEWBORN TACNA - Ticona, Manuel (2015)
OBJECTIVE: To obtain curve itself, representative of the population of Tacna and compared with standard curves Lubchenco intrauterine growth. MATERIALS AND METHODS: Prospective enrollment of successive live newborns, weighing, diagnosis of gestational age by last menstrual period, excluding maternal and fetal pathology; discarding smoking and maternal malnutrition; the Perinatal Information System (CLAP-PAHO / WHO) and statistics required tests was used. RESULTS: 8,735 living RN selected in six years (1995-2000); 40 weeks gestation was the most representative (36.7% of RN), with an average weight of 3514g. ± 403 g (percentile 10, 50 and 90 were 2983, 3503 and 4062 g. Respectively). These data were significantly different from Lubchenco. CONCLUSIONS: intrauterine growth curves (CCIU), according to weight, height, head circumference and weight index tacneña a well-selected population showed no difference with Lubchenco growth curves.